The Kochia and Dicamba Story. Issue 1 (13th March 2014) - Sandall, Leah; Lee, Don; Bernards, Mark; Crespo, Javier
Abstract : Herbicides are standard weed management tools for producers. This lesson examines the development of herbicide resistant‐weeds and research conducted to help predict and prevent this resistance. Discussion on populations of organisms and evolution of these populations is included.